Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1258/jtt.2009.090907
|View full text |Cite
|
Sign up to set email alerts
|

Home telemonitoring and quality of life in stable, optimised chronic obstructive pulmonary disease

Abstract: We conducted a six-month randomised controlled trial of home telemonitoring for patients with chronic obstructive pulmonary disease (COPD). A total of 40 stable patients with moderate to severe COPD who had completed pulmonary rehabilitation took part. They were randomised to receive standard care (controls) or standard care plus home telemonitoring (intervention). During the monitoring period, patients in the telemonitoring group recorded their symptoms and physical observations twice daily. The data were tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(96 citation statements)
references
References 33 publications
0
96
0
Order By: Relevance
“…Other studies were excluded because of lack of telemonitoring or comparators. Four RCT (Kamei et al, 2011a(Kamei et al, , 2011bLewis et al, 2010aLewis et al, , 2010b) that were based on the same samples but reported different outcomes were also included ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies were excluded because of lack of telemonitoring or comparators. Four RCT (Kamei et al, 2011a(Kamei et al, , 2011bLewis et al, 2010aLewis et al, , 2010b) that were based on the same samples but reported different outcomes were also included ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Countries of origin of the nine articles included the UK (n = 2; Lewis et al, 2010aLewis et al, , 2010b, Japan (n = 2; Kamei et al, 2011aKamei et al, , 2011b, Denmark (n = 1; Sorknaes et al, 2011), Italy (n = 1; Vittaca et al, 2009), Australia (n = 1; Shany et al, 2010), the Netherlands (n = 1; Trappenburg et al, 2008), and Spain (n = 1; de Toledo et al, 2006). THMTN duration ranged from 1 month (Sorknaes et al, 2011) to 12 months (de Toledo et al, 2006;Shany et al, 2010;Vittaca et al, 2009) (Table 1).…”
Section: Country Of Publication and Duration Of Thmtnmentioning
confidence: 99%
“…In particular, it can be noticed that the benefit of telemedicine interventions were at best small in studies including education on self-care [13,16] or the patients were already followed in the center in which the experiment took place [14]. Interestingly, when education on self-care was offered only to telemedicine group, the reduction of hospitalizations in the intervention group was more evident [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Five studies used the St. George's Respiratory Questionnaire (SGRQ). A statistically and clinically (>= 4 points) significant improvement in SGRQ score was reported only by Koff et al Two trials documented a non-statistically significant change >= 4 points in SGRQ in telemonitoring group compared with control group [18,21] and four studies did not show differences in quality of life between groups [11,13,14,16].…”
Section: Effect On Quality Of Lifementioning
confidence: 94%
See 1 more Smart Citation